2020
DOI: 10.1186/s12885-020-07409-9
|View full text |Cite
|
Sign up to set email alerts
|

GLUT-1 as a predictor of worse prognosis in pancreatic adenocarcinoma: immunohistochemistry study showing the correlation between expression and survival

Abstract: Background Various parameters have been considered for predicting survival in pancreatic ductal adenocarcinoma. Information about western population is missing. The aim of this study is to assess the association between Glucose transporter type 1 (GLUT-1) expression and prognosis for patients with PDAC submitted for surgical resection in a European cohort. Methods Retrospective analysis of PDAC specimens after pancreatoduodenectomy a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Inhibition of HIF1A by chetomin decreases the expression of downstream gene-encoding of SLC2A1 in MPNST cell lines [ 25 ]. Corresponding to our study, high expression of SLC2A1 has been found to be associated with inferior outcomes in various malignancies in adults, including pancreatic cancer, colorectal cancer, breast cancer, lung cancer, and others [ 27 , 28 , 29 , 30 ]. Accordingly, pediatric cancers overexpressing SLC2A1, like adrenocortical carcinomas and liver vascular tumors, have worse prognosis than SLC2A1-negative tumors [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 71%
“…Inhibition of HIF1A by chetomin decreases the expression of downstream gene-encoding of SLC2A1 in MPNST cell lines [ 25 ]. Corresponding to our study, high expression of SLC2A1 has been found to be associated with inferior outcomes in various malignancies in adults, including pancreatic cancer, colorectal cancer, breast cancer, lung cancer, and others [ 27 , 28 , 29 , 30 ]. Accordingly, pediatric cancers overexpressing SLC2A1, like adrenocortical carcinomas and liver vascular tumors, have worse prognosis than SLC2A1-negative tumors [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 71%
“…et Medina Villaamil et al, 2011;Starska et al, 2015;Barron et al, 2016;Schlößer et al, 2017;White et al, 2018;Kuo et al, 2019;Heydarzadeh et al, 2020;Achalandabaso-Boira et al, 2020). Overexpression of GLUT2 is found in cancers of the breast, colon, liver, pancreas and small intestine (Tomita, 1999;Godoy et al, 2006;Hamann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…GLUT1 distributes widely in human body, its expression tends to be low in normal tissues or benign lesions compared with corresponding tumor tissues, which partially indicates a rapid development and poor prognosis 15 . Increasing evidences suggested that GLUT1 expression positively correlated with survival time and worse response to treatment 16 - 19 . But the mechanisms remain unclear in PAAD, especially the regulatory network of GLUT1 and competitive endogenous RNAs (ceRNAs), as well as the relationship between GLUT1 and malignant biological behaviors of PAAD.…”
Section: Introductionmentioning
confidence: 99%